Molecular Identification of Fungi Isolated from Selected Varieties of Low Postharvest Physiologically Deteriorated Cassava (Manihot esculenta Crantz) - Alimi , J. P.; Ahemen, S. A.; Alimi, J. O.; Balogun, D. A.; Oke, O. A. (Research Advances in Microbiology and Biotechnology Vol. 3, 2023)
The use of molecular technologies to further expanciate on the morphology-based taxonomy of fungi helps in the differentiation of fungal species and varieties. The study investigated the properties of microorganisms isolated from high quality cassava flours produced from low postharvest physiologically deteriorated (PPD) cassava using molecular identification. Wholesome five varieties of cassava were used out of which four varieties were of yellow-fleshed low PPD cassava while one variety was of high PPD. The cassava roots were subjected unit operations such as peeling, washing, grating, pressing, pulverization and were dried in a flash dryer at 120°C for 8 minutes and subsequently milled into flour with cyclone hammer mill having a screen size of 250 µm apertures. The high quality cassava flour produced was tested for total viable fungal and bacterial count; fungi isolated have been further characterized and identified using molecular techniques. Characteristic fungal counts obtained were subjected to analysis of variance (ANOVA) using Statistical Package for Social Sciences (SPSS version 25.0) and significant means were separated applying Duncan Multiple Range Test. The isolated and identified organism as revealed by the DNA results are Saccharomyces cerevisiae, Aspergillus oryzae, Aspergillus niger, Rhizopus stolonifera, Penicillium sp, Aspergillus oryzae and Rhizopus microsporum. Aspergillus niger’ is noted to be safe for application in industries (production of enzymes such as amylases, lipases, celluloses, xylanases and proteases), medical and agricultural use. Total viable bacterial count and fungal count of the high quality cassava flours prepared from IITA-TMS-IBA-011368, IITA-TMS-IBA-070593, IITA-TMS-IBA-011412, IITA-TMS-IBA-011371 and TMEB 419 cassava varieties were within the permissible limit of the microbial load of food allowed for human consumption according to the Standard Organization of Nigeria and Codex Alimentarius.